Accounting for photosystem I photoinhibition sheds new light on seasonal acclimation strategies of boreal conifers - Grebe, Steffen (Journal of experimental botany, 2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology.